Kierkegaard and Johannes Tauler on Faith, Love, and Natural Desire for God: A Way beyond a Catholic/Protestant Impasse - Barrett, Lee C. (Toronto journal of theology, 2016)
For almost a century, an intermittent battle has been waged in Kierkegaard studies concerning the Dane's understanding of the Christian life and salvation. One way of posing the contentious question is this: on the issues of faith and love, justification and sanctification, and nature and grace, was Kierkegaard more Lutheran, or was he more Catholic? This article argues that this ambiguity about Kierkegaard's soteriological predilections is understandable, for his writings do not fall into the neat categories defined by post-Tridentine Catholicism or scholastic Lutheran orthodoxy. Rather than advocating for either of those doctrinal positions, his writings on justification and sanctification, nature and grace, and eros and agape continue a more nuanced trajectory rooted in some of the spiritual writers of the Middle Ages and extended later by the pietists. That trajectory defies the polemical binary classifications typical of the late sixteenth century. To clarify this alternative orientation, we will sketch the basic contours of Kierkegaard's scattered remarks about soteriology, and then explore their similarity to many of themes of Johannes Tauler (1300-1361), one of the most influential spiritual writers of the late medieval period. Tauler used a more metaphysical vocabulary to express a theological vision that exhibited significant formal parallels to Kierkegaard's later subversion of Catholic and Lutheran scholastic dichotomies. For both Tauler and Kierkegaard, the attractive beauty of God's self-giving love serves as the foundation for a theological vision that unites faith and love, justification and sanctification, and nature and grace.